New Indole Glycosides from Aesculus chinensis var. chekiangensis and Their Neuroprotective Activities - Zhang, Nan; Cao, Shijie; Huang, Weixing; Li, Pan; Kang, Ning; Ding, Liqin; Qiu, Feng (Molecules (Basel, Switzerland), 2019)
The dried seeds of Aesculus chinensis Bge. var. chekiangensis (Hu et Fang) Fang, called “Suo Luo Zi”, have been used in traditional Chinese medicine. Nevertheless, most studies have been focused on components of less polarity fractions. In this research, twelve indoles, including six new indole glycosides (1–6) as well as six known analogs were isolated from the polar portion which has been seldom studied. This is the first description of N-glucosylated indoles obtained from the genus of Aesculus. Structures of the new compounds (1–6) were elucidated based on comprehensive interpretation of HRESIMS, 1D and 2D NMR. Additionally, the neuroprotective activities of the N-glucosylated indoles were evaluated for the first time indicating that compounds 1–5 and 9–10 exhibited moderate neuroprotective activities. Further cytotoxicity tests of isolates 1–10 on three human tumor cell lines suggested that none of these compounds were cytotoxic (IC50 > 50 μM).